Use of anti-inflammatory drugs by patients admitted with small or large bowel perforations and haemorrhage. Issue 6465 (2nd February 1985) - Langman, M J; Morgan, L; Worrall, A
Abstract : The intake of anti-inflammatory drugs by 268 patients with colonic or small bowel perforation or haemorrhage was compared with that by a group of patients, matched for age and sex, with uncomplicated lower bowel disease. Patients with perforation or haemorrhage were more than twice as likely to be takers of anti-inflammatory drugs, but no association was detected with the intake of other types of drugs, particularly cardiovascular drugs. The association between complicated lower bowel disease and intake of anti-inflammatory drugs may be causal.